Method of determination of circadian index in patients after septoplasty - I. V. Kastyro (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
60 men of 25-39 years (10 healthy men and 50 men with nasal septum deviation (NSD)) had daily Holter monitoring of electrocardiogram. Patients with. NSD who had septoplasty were divided into groups: without anesthesia, analgin, diclofenac, ketorol and ketamine - 1st, 2nd, 3rd, 4th and 5th groups correspondingly. Healthy people were related to the group 0 (comparison group). Monitors in 1st-5th groups were set 30 minutes before and. operation and. were took away in a day. Circadian index (CI) was calculated by the deviation of ST segment from contour (CST) and. by heart rate (HR). Approximation analysis of CI was realized, within each group, Student analysis was realized between the groups. Approximation coefficients were from 0,6 to 0,87. Differences of circadian indices on CST and. HR were revealed only in the 1st group (p < 0,05). Intergroup analysis showed that groups 0 and. 3 were comparable, decrease of CI was revealed in the 4th and. 5th groups (p < 0,05). The 2nd group had tendency to the decrease of CI. CI can be calculated non only by HR but also by deviation of CST that points to the significance of CST not only as a marker of ischemia but also as the index of tension of vegetative nervous system.